(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
Attending the regulation of the phenomenon of gender violence in our legal system, there is a need to study and analyze the role of the popular accusation in such procedures. More so when the Autonomous Communities, and especially Madrid, have enabled, in their specific legislation on the subject, the assistance of the Regional Administration as popular accusation in the procedures followed in the territory of the Community, regarding crimes within the scope of violence against women, in a rightful aim to act against this scourge of our society, but by a legislative technique which has been widely criticized by the scientific doctrine and should be contrasted in light of current constitutional jurisprudence on the exercise of popular action in the Spanish legal system.